Local blood flow in peripheral nerves and their ganglia: Resurrecting key ideas around its measurement and significance. Issue 6 (11th January 2018) - Zochodne, Douglas W.
ABSTRACT: Over 3 decades ago, seminal work by Phillip Low and colleagues established exquisite physiology around the measurement of nerve blood flow (NBF). Although not widely explored recently, its connection to the clinic has awaited human methodology. While human studies have not achieved a convincing level of rigour, newer imaging technologies are offering early information. The peripheral nerve trunk has parallel blood flow compartments that include epineurial flow dominated by arteriovenous shunts and downstream endoneurial blood flow (EBF). NBF and EBF have lower values than central nervous system blood flow, lack autoregulation yet have sympathetic and peptidergic neurovascular control. Contrary to expectation, injury to nerves is often associated with rises in NBF rather than ischemia, a finding of biological interest corroborated by human studies. Despite its potential importance, quantitative human measurements of EBF and NBF are not yet available. However, with development, careful NBF analysis may present new insights into nerve disorders. Muscle Nerve 57 : 884–895, 2018